Growth Of Financial Performance PT. Gresik Cipta Sejahtera (GCS) Year 2011-2014 Using Financial Ratio Analysis - Boni A Pasaribu (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2021)
Assessment of financial performance can be known through a report, a report which describes the growth of the company's financial performance in certain periods. The report is called the financial statements. In order to make the financial statements useful for the parties concerned, it is needed to conduct analysis of the relations of the items in the financial statements which is often called financial statement analysis.The purpose of this study, to determine the growth of financial performance at PT. Gresik Cipta Sejahtera Medan in 2011-2014 based on the analysis of liquidity, leverage, and profitability.The data analysis method used is comparative descriptive method using a ratio measurement of liquidity, leverage, and profitability. Based on the current ratio, inventory to net working capital and debt to equity ratio, the company is in good shape, although they fluctuate during the period from 2011-2014. Based on the quick ratio, cash ratio, debt ratio, gross profit margin, net profit margin, ROI, and ROE, the company is in unfavorable circumstances, thus encouraged to improve efficiency.